Novel dual‐mode filters implemented by quarter mode folded substrate integrated waveguide. Issue 17 (20th May 2021) - Yang, Ling; Xu, Feng; Liu, Qing; Qiang, Jingxia; Zhan, Junlin
Abstract: Two dual‐mode filters implemented by folded substrate integrated waveguide (FSIW) are proposed here. The high order modes (TE103 and TE301 ) in the FSIW cavity are employed to realize the function of filters. The non‐resonating node TE202 mode is employed in the first filter to realize the transmission zero below the passband. A metal pin and an L‐shaped slot are used in another dual‐mode filter to restrict the parasitic mode, TE202 mode. The proposed FSIW dual‐mode filters with simple structures exhibit compact size and good frequency selectivity. As per knowledge, it is the first time that the quarter mode FSIW (QMFSIW) cavities are utilized to design the multimode filters. The measured results agree well with the simulated ones, which validates the feasibility of the compact dual‐mode filters based on the technology of double‐layered FSIW.